An Exploration of Adolescent Psychological Issues in the Netflix Series Adolescence (2025) - Rosalia Floriani; Arin Mantara Anggawirya; Survey Sijabat; Nurul Istiqomah; Evelin Giovani (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to examine the portrayal of adolescent identity crisis through the character Jamie in the Netflix series Adolescence (2025) and to analyze the psychosocial factors influencing his identity formation. This research uses a qualitative descriptive methodology to analyze narrative elements across four episodes, focusing on identity conflict, peer relations, family dynamics, and digital media influence. Grounded in Erik Erikson’s identity development theory, the research highlights that adolescent identity formation is contingent upon prior developmental stages. Jamie’s experience of profound feelings triggers maladaptive behaviors, including violent acts. Both Jamie and his close friends are marginalized due to perceived physical unattractiveness and social unpopularity, resulting in sustained peer victimization. Psychosocial influences identified include parental relationships marked by inadequate communication, peer rejection and bullying, and emerging sexual awareness during puberty. Despite a nonviolent and harmonious family environment, ineffective parental engagement contributes to Jamie’s emotional withdrawal. Furthermore, the research underscores the significant impact of social media as a double-edged factor, facilitating social connectivity and information acquisition while simultaneously exacerbating feelings of alienation, anxiety, and exposure to cyberbullying. Without adequate adult guidance, adolescents may internalize harmful ideologies, such as misogyny and distorted masculinity constructs, adversely affecting their mental health. The findings advocate for enhanced family communication, supportive peer environments, and structured digital literacy education to foster healthy adolescent psychosocial development.